Peran public relations dalam meningkatkan kepercayaan publik terhadap bank syariah di era digital - Daris, Daris (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of Public Relations (PR) in increasing public trust in Islamic banks in the digital era. The main issue raised is the low level of literacy and trust among the public regarding the Islamic financial system amid the rapid digitization of banking. This study uses a qualitative descriptive method with a literature study approach to various academic journals relevant to the themes of communication and Islamic finance. The results of the study show that PR has a strategic role in building a positive image, increasing information transparency, and creating educational two-way communication between institutions and the public. The challenges faced include public misperceptions of sharia principles, limited digital literacy of PR resources, and competition with conventional financial institutions and fintech. Therefore, PR strategies need to be directed towards strengthening communication based on Islamic values that are adaptive to technological developments and the needs of modern society. With a professional and innovative PR role, public trust in Islamic banks can increase and have a positive impact on the growth of the national Islamic finance industry.